The Effect Of Senior Exercise In A Sitting Position Using Cloth On Cardiovascular Load - MUHAMMAD ZAFFARUL AZZALNA AL AZHAR; Arin Supriyadi (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Introduction: The aging process causes a decline in physiological functions, including the cardiovascular system, which increases the risk of hypertension and heart disease in the elderly. Physical activities like elderly gymnastics have been shown to maintain fitness and reduce the risk of these diseases. However, mobility limitations and concerns about injury make it difficult for some elderly individuals to participate. Therefore, safe and effective modifications of gymnastics are needed, one of which is seated exercises using fabric to assist movements without adding excessive strain to the body. Objective: This study aimed to determine the effect of seated elderly exercise using a cloth as an aid on cardiovascular load in older adults.. Method: This quantitative study used a pretest–posttest single group design. The subjects were older adults in Mantren Hamlet, Klodran Village, Colomadu District, Karanganyar Regency, who met the inclusion criteria. The intervention was conducted in 10 sessions, each lasting 1 hour (10 minutes warm-up, 40 minutes core exercise, and 10 minutes cool-down). Blood pressure, oxygen saturation, and pulse rate are measured before and after the intervention using a sphygmomanometer and oximeter. Data are analyzed using the Shapiro–Wilk normality test and paired t-test or Wilcoxon test as appropriate. Results: Analysis of the study shows that the average systolic and diastolic blood pressure decreased in the first week and fourth week after the intervention, while SpO₂ values remained within the normal range. The normality test indicated that the data did not follow a normal distribution, so the test was continued using the Wilcoxon test. The Wilcoxon test results showed a significant difference between the values before and after the intervention in all physiological parameters (p < 0.05), marked by a decrease in blood pressure and an increase in SpO₂ values after the intervention. Conclusion: The intervention applied was proven to have a positive effect on cardiovascular and oxygenation parameters in the elderly, as indicated by a significant decrease in blood pressure and an increase in oxygen saturation. This study shows that the intervention has the potential to be an effective approach to support cardiovascular health in the elderly, although further research with a larger sample and more optimal control of variables is still needed to strengthen the generalization of the findings